GAMBARAN KEPATUHAN KONTROL PASIEN PASKA STROKE BERDASARKAN FAKTOR DEMOGRAFI - Sofi Novia Andriani; Ali Hamzah; Lina Erlina; Hotma Rumahorbo (UPPM. Poltekkes Kemenkes Bandung, 2022)
This research was motivated by the high incidence and mortality of stroke patients in Indonesia every year. Strokes can also cause disability and even death and often occur repeatedly, so it is necessary to control risk factors that can prevent the occurrence of these attacks, among others by exercising routine control. Routine control needs to be followed by adherence from the patient so that the effectiveness of treatment and complications that may arise can be monitored and controlled. This study aims to determine the compliance of post-stroke control patients based on demographic factors in Dr. Salamunun Hospital. The research method used is descriptive method, with a total sample of 191 people obtained through total sampling techniques. The data obtained came from secondary data, namely from the patient's medical record report. The results showed that demographic factors had a contribution to patient compliance, which was based on the age factor of almost half (33.5%) patients aged> 65 years and more than half of the respondents were male patients (68.9%) obedient do control post stroke. Meanwhile, according to the level of education, almost half (37.8%) of the graduates who were educated were compliant to control, and almost half (44.4%) of those who worked as compliant entrepreneurs exercised control after stroke and according to the status of patient visits that adhered to control, which was partly besaar (86.7%) old patients. Thus it can be concluded that only a small proportion (23.6%) of stroke patients who adhere to routine control after they have had a stroke. For this reason it is advisable for nurses to always remind the control schedule of both the patient and the patient's family after stroke about 2-3 days before the control schedule via social media.